A dark and stormy knit - Canadeo, Anne, 1955- (Canadeo, Anne, 1955- Black sheep knitting mystery., 2014)
"The Black Sheep Knitters are initially amused by the antics of the Knit Kats - a local knitting graffiti group who apply their stitching to public protest. Like covering the new parking meters along Main Street with knitted hoods that have silly cat faces. The amusing act of civil disobedience causes a stir in quiet Plum Harbor. But it's not the first time the Knit Kats have made local news. The group proudly touts full responsibility on their website, which is complete with photos of the members - identities concealed by elaborate disguises and mysterious pseudonyms. The Knit Kats mean no harm, they claim, but are dedicated to brightening the landscape and raising awareness. Which no one can dispute...until a dead body turns up, covered in stitches that bear the distinct paw print of Knit Kat mischief. Detectives investigating the crime soon discover that Phoebe Myers, Maggie Messina's assistant, has been auditioning for a spot in the Knit Kat group. When Phoebe is implicated, the Black Sheep take on the tangle of clues, determined to clear her name. Are the mysterious Knit Kats truly a vicious cabal? Or, is some copy-cat knitter trying to pin the group with this murderous wrap? Maggie reminds her friends that all cats look the same in the dark. But the Black Sheep know better about killers, who always leave behind a tell-tale thread. With clever detection skills and their own, irrepressible curiosity, Maggie and the knitting friends soon uncover the truth about the Knit Kats -- and snag the guilty stitcher"--